Applied of Synthesis Furfural Based on Cassava Stems (Manihot utilissima) As Fuel Additive to Gasoline - Lismeri, Lia; Riyadi, Lutfia Rahma; Darni, Yuli; Nugrahini, Panca; Azhar, Azhar; Lesmana, Donny (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
Biofuel is an option to reduce CO2 generated by vehicles. In this study, synthetic crude furfural from cassava stems was blended as fuel additive to gasoline (Pertalite) and then induced by electromagnetic field. Analysis were carried out on engine performance and exhaust emissions produced by Kohler engines. Variations formed by samples crude furfural and commercial furfural (C5H4O2), then time variations of electromagnetic induction for 0 and 30 minutes. The blending composition of gasoline and furfural in a mixture of 1,500 ml fuel is 96% : 4%. The best results from increasing torque, cranking power and saving fuel consumption were obtained from variations in the use of crude furfural additives induced by electromagnetic fields (CFE). Exhaust emissions produced by pure Pertalite are still lower than fuels with furfural additives. The content of water and impurities in crude furfural causes the additive unmixed with Pertalite which is non-polar and hydrophobic.